The Singapore-India Connection: A Tale of Two Industrial Parks - YEOH, Caroline (Institutional Knowledge at Singapore Management University, 2004)
In recent times, Singapore has, as part of its regionalisation strategy, established industrial parks in various countries, including China, Vietnam, and India. The parks are marketed as a winning combination of the host country’s unique location advantages and Singapore-style efficiency and management know-how. Singapore’s foray into India, in particular, was marked by the setting up of the ITPL in Bangalore; a development that met with great success. However, with global businesses shifting interests towards India, and competing industrial parks emerging to meet the increasing demand, ITPL is faced with stiff competition from other industrial parks; and Singapore has since announced its partnership in phase 3 of another industrial park, the locally set-up HITEC City. This paper compares the pull factors and constraints of ITPL with phase 1 and 2 of the HITEC City and also differentiates between these two sites, which both gain leverage from India’s cheap plentiful labour, through the use of in-depth case studies. It also discusses the likely effects on HITEC of its new Singapore connection. Through this comparison, the factors that influence tenants in these industrial parks – and the influence of the Singapore connection on these factors - will be made clear.